Celastrol attenuates amphiregulin expression by inhibiting MAPK signaling pathway in triple-negative breast cancer cells - Sangmin Kim; Daeun You; Yisun Jeong; Sun Young Yoon; Eunji Lo; Jeong Eon Lee (Elsevier, 2022)
Background: Amphiregulin (AREG) plays an essential role in the metastasis and angiogenesis of various cancers. Purpose: The objective of this study was to investigate the pharmacological effects of celastrol on AREG expression in triple-negative breast cancer (TNBC) cells. Methods: We analyzed the prognostic value of AREG, EGF, TGFA, and HB-EGF mRNA expression in TNBC patients. Cell proliferation was analyzed by MTT assay and colony-forming assay. Levels of protein and gene expression were analyzed by ELISA, Western blotting, confocal microscopy, and real-time PCR, respectively. The expression of angiogenic proteins was analyzed by using the Human angiogenesis array kit. Cell invasiveness was analyzed by Boyden chamber assay. Results: Our results showed that abnormal AREG induction remarkably decreased the relapse-free survival (RFS) rate of TNBC patients, whereas epidermal growth factor (EGF), transforming growth factor-alpha (TGFA), or heparin-binding EGF-like growth factor (HBEGF) demonstrated no effect on RFS rate. In addition, the growth of TNBC cells was prevented by drugs targeting EGFR such as neratinib or lapatinib. On the contrary, cell growth and invasion were enhanced by AREG treatment. Interestingly, celastrol reduced AREG expression and the growth of TNBC cells. Furthermore, we found that levels of AREG expression were reduced by a potent inhibitor of MEK1/2, binimetinib (BIN). Our results showed that celastrol significantly decreased the levels of ERK phosphorylation in TNBC cells. Finally, we observed that celastrol also suppressed the AREG-induced EGFR signaling pathway. Taken together, these results suggest that celastrol can downregulate AREG expression by inhibiting the MEK/ERK signaling pathway. In addition, the AREG-induced EGFR signaling pathway was inhibited by celastrol. Conclusion: Celastrol can be an effective drug for treating TNBC by inhibiting AREG/EGFR signaling pathways.